2017
DOI: 10.1017/s1355617717000182
|View full text |Cite
|
Sign up to set email alerts
|

Social Behavior and Impairments in Social Cognition Following Traumatic Brain Injury

Abstract: Method: Forty participants with TBI and 32 matched healthy participants completed a battery of tests assessing the three functions of interest. In addition, self-and proxy reports of pre-and post-injury behaviour, mood, and community integration were collected. Results:The TBI group performed significantly poorer than the comparison group on all tasks of emotion recognition, understanding intention and on one task of response selection. Ratings of current behaviour suggested significant changes in the TBI grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 83 publications
1
39
1
Order By: Relevance
“…Contrary to our hypothesis, we found that theory of mind (ToM), empathy, emotion recognition and behavioural control were not associated with restrictions in participation three to four years after stroke. This is inconsistent with the reported relationship between emotion perception and participation in stroke in a previous study (Cooper et al, 2014) and with the literature on the relationship between social cognition and participation in moderate to severe TBI (May et al, 2017;Ubukata et al, 2014;Westerhof-Evers et al, 2018). Several factors may contribute to these contradictory findings.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Contrary to our hypothesis, we found that theory of mind (ToM), empathy, emotion recognition and behavioural control were not associated with restrictions in participation three to four years after stroke. This is inconsistent with the reported relationship between emotion perception and participation in stroke in a previous study (Cooper et al, 2014) and with the literature on the relationship between social cognition and participation in moderate to severe TBI (May et al, 2017;Ubukata et al, 2014;Westerhof-Evers et al, 2018). Several factors may contribute to these contradictory findings.…”
Section: Discussioncontrasting
confidence: 80%
“…Studies in patients with moderate to severe traumatic brain injury (TBI) support the relationship between social cognition and participation (May et al, 2017;Ubukata et al, 2014) and indicate that social cognition is an even stronger predictor than executive functioning (Westerhof-Evers, Fasotti, van der Naalt, & Spikman, 2018). Despite evidence for the role of social cognition in participation in severe TBI, the literature on this relationship in stroke patients is limited to the study of Cooper et al (2014), who report an association between emotion perception deficits and reduced participation, as well as a reduced quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Differences generally are small (e.g., accounting for <10% of variance in scores) and are mostly for threat-related affective displays. Analysis of 14,000 samples of written and spoken language showed that women also used more emotion words (e.g., happy, certainty, nervous, and hate) than men, and fewer swear words (31), although again effect sizes were small [i.e., [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Sex Differences In Social Cognition In Typical Adultsmentioning
confidence: 99%
“…The review focuses on two aspects of social cognition that have been studied in TBI: recognition of emotions from facial affect; and Theory of Mind (ToM), the ability to attribute mental states to oneself and others, and use that information to make predictions about others' actions (9). We chose these two aspects of social cognition because they have been linked to broader social outcomes like quality of life and social reintegration, both conceptually (10)(11)(12), and empirically (13)(14)(15)(16)(17)(18)(19)(20). We consider data from typical adults and adults with TBI, in the broader context of common stereotypes about social skills and behaviors in men vs. women.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these findings imply that cognitive, affective and conative ToM may be predicted imminently through the individual differences in structures of different neural systems-the Cerebro-Cerebellar Mentalizing Network, Salience Network, and Mirror Neuron/Empathy Network, in each turn. TBI patients were observed to perform markedly worse than the healthy-volunteer control group with regard to all of the tests of emotion recognition, intention-comprehension, and on one particular task of response selection that together describe social learning [18].…”
Section: Introductionmentioning
confidence: 87%